2023
DOI: 10.3389/fmed.2023.1109411
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for clinical decision support for monitoring patients in cardiovascular ICUs: A systematic review

Abstract: BackgroundArtificial intelligence (AI) and machine learning (ML) models continue to evolve the clinical decision support systems (CDSS). However, challenges arise when it comes to the integration of AI/ML into clinical scenarios. In this systematic review, we followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), the population, intervention, comparator, outcome, and study design (PICOS), and the medical AI life cycle guidelines to investigate studies and tools which address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“… 47 Interestingly, a study has reported that AI has also the potential to perform in emergency circumstances, assisting in monitoring cardiovascular patients in ICUs. 40 …”
Section: Discussionmentioning
confidence: 99%
“… 47 Interestingly, a study has reported that AI has also the potential to perform in emergency circumstances, assisting in monitoring cardiovascular patients in ICUs. 40 …”
Section: Discussionmentioning
confidence: 99%
“…This focus has necessitated the creation and deployment of intricate and precise algorithms that have been purpose-built for specific applications. These include, but are not limited to, Cobb angle analysis for assessing spinal deformities, breast cancer diagnosis, and providing support for patient monitoring in cardiovascular intensive care units [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classifiers enhanced the prognosis of ICU patients beyond standard techniques by capitalizing on detected structural temporal trends. This innovative approach holds promise for predicting AEs in critical care settings, aiding clinicians in timely interventions to prevent or mitigate AEs [31]. The research underscores that integrating ML methodologies with high-quality clinical data in ICU environments can proficiently predict life-threatening events, enabling prompt interventions [55].…”
Section: Analytical Approaches For Identifying Best Practices and Ref...mentioning
confidence: 99%
“…They analyze patient data, guidelines, and literature to suggest treatment plans, med-dosages, and interventions. Considering unique patient characteristics, AI-driven systems enhance decisionmaking and improve patient care[31].…”
mentioning
confidence: 99%